2006
DOI: 10.1002/ajmg.a.31563
|View full text |Cite
|
Sign up to set email alerts
|

Two novel point mutations in the long‐range SHH enhancer in three families with triphalangeal thumb and preaxial polydactyly

Abstract: Spatio‐temporal expression of sonic hedgehog (SHH) is driven by a regulatory element (ZRS) that lies 1 Mb upstream from SHH. Point mutations within the highly conserved ZRS have been described in the hemimelic extra toes mouse and in four families with preaxial polydactyly [Lettice et al., 2003]. Four North American Caucasian families were identified with autosomal dominant triphalangeal thumb. DNA from 20 affected and 36 unaffected family members was evaluated by sequence analysis of a 774‐bp highly conserved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
83
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 21 publications
3
83
0
1
Order By: Relevance
“…It was shown that five point mutations residing in the highly conserved sequence of ZRS were associated with congenital preaxial polydactyly (Lettice et al 2003;Gurnett et al 2007), mutations in the chicken Lmbr1 are linked to chicken polydactyly (Huang et al 2006), and Shh was responsible for the digit duplication activity in chick embryos (Riddle et al 1993). Unfortunately, we failed to identify any pathogenic mutations of these genes in the SD4 patients from the Chinese family.…”
Section: Resultsmentioning
confidence: 86%
“…It was shown that five point mutations residing in the highly conserved sequence of ZRS were associated with congenital preaxial polydactyly (Lettice et al 2003;Gurnett et al 2007), mutations in the chicken Lmbr1 are linked to chicken polydactyly (Huang et al 2006), and Shh was responsible for the digit duplication activity in chick embryos (Riddle et al 1993). Unfortunately, we failed to identify any pathogenic mutations of these genes in the SD4 patients from the Chinese family.…”
Section: Resultsmentioning
confidence: 86%
“…The Arx GABAergic enhancer represents a good candidate as a noncoding sequence that, when mutated, may lead to Arx-specific silencing restricted to forebrain interneurons, and therefore causes the development of related neuropathological conditions (e.g., epilepsy, mental retardation, and motor deficits). Mutations in the enhancer elements of developmental genes like Shh, Ret, Pitx2, Gli3, and Pax6 have been already described to cause human congenital diseases (Emison et al, 2005;Kleinjan and van Heyningen, 2005;Gurnett et al, 2007). Thus, it would be valuable to perform a mutational screening of this Arx enhancer sequence in those highly related neurological disorders in which mutations in the Arx coding region failed to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…31 In previous PPD studies, there are only 13 pedigrees in which the responsible point mutations were identified. 13,16,17,23,25 On the other hand, pathogenic mutations are still remained unidentified in most PPD families. 8,11 -13,23 Furthermore, although the 7 pathogenic point mutations identified in above 13 pedigrees were all located in the ZRS of shh, these mutation sites were scattered in the ZRS and no clustering of mutations toward domain-like structure was evident.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, no known regulatory domain had been defined by bioinformatics method, so far. 13 These information suggested that the network of shh regulation was much complex and is poorly understood. Recently, the copy number variations, such as duplication, has been shown to be the underlying cause for human genetic disorders.…”
Section: Discussionmentioning
confidence: 99%